Giving language to horticultural therapy: framing horticultural therapy through the lens of empirically supported therapies - Ascencio, Jaime M., author; Rickard, Kathryn, advisor; Prince, Mark, advisor; Graham, Dan, committee member; Shillington, Audrey, committee member (Colorado State University. Libraries, 2020)
Horticultural therapy, a plant-based intervention for reaching client goals, is an under-researched yet promising treatment modality for psychiatric disorders. This study aimed to forge a connection between empirically supported therapies (ESTs) and horticultural therapy's interventions by describing how EST methods were used in horticultural therapy. A horticultural therapy proof-of-concept study incorporated behavioral, positive, and humanistic ESTs with youth with disabilities and at-risk youth. The largest positive impacts of the intervention were on clients' prevocational skills, social skills, and gardening skills. No change was detected on measures of mindfulness, resilience, nature relatedness, or strengths use. The impact on depression yielded mixed results, and a small worsening was seen in the self-report of anxiety, strengths use, and emotion regulation. This study demonstrated that horticultural therapy utilizes components of a variety of ESTs and its impact can be quantitatively evaluated.
Keywords: behavioral therapy; empirically supported therapy; nature-based therapy; ecotherapy; at-risk youth; horticultural therapy